Netflix's Global Market Entry and Adaptation Strategies Critical Review - Serenade, Vincensia; Umar; Jati, Intan Mustika (SAFE-Network, 2024)
This review analyzes Netflix's evolution from a local DVD rental service to a global streaming leader with 221 million subscribers across 190 countries. It focuses on Netflix's strategies for international expansion, including its innovative distribution methods, personalized user experiences, and localization efforts. By adapting its business model to meet diverse cultural and regulatory demands, Netflix has successfully navigated significant challenges such as cultural barriers and competition from local and global players like Disney+ and Amazon Prime. The review synthesizes insights from two academic articles: The Business Strategy Analysis of Netflix by Yu-Hao Hsiao, which emphasizes Netflix’s subscription model and technological advancements, and Strategy for Growth and Market Leadership: The Netflix Case by Kishwar Joonas et al., which explores marketing strategies and competitive dynamics. Key findings highlight the importance of original content development, technological innovations like AI and machine learning for user engagement, and effective localization strategies. This analysis aims to provide valuable perspectives for other technology companies seeking global expansion while maintaining a competitive edge. Ultimately, it underscores the significance of aligning long-term strategic vision with short-term tactical adaptations in navigating the complexities of the global entertainment landscape. Through this critical evaluation, we gain insights into how multinational corporations can thrive in an increasingly digitalized world.